Design And Implementation Of It Helpdesk Application Using Knowlegde Management System Approach: Design And Implementation Of It Helpdesk Application Using Knowlegde Management System Approach - Dhani Farhansyah; Septi Andryana; Winarsih Winarsih (Jurnal Mantik, 2020)
The agency, Helpdesk is part of a department that executes methods for collecting data from various sources and is assigned to serve and respond to user needs. In the development of Helpdesk this can provide services, solve problems and provide solutions to the problems of hardware, software, network, and applications or things related to office work. The Web helpdesk also helps to accelerate information and address problems. The IT assistance help is still applied to solve the problem of every institution currently only send email, via phone and chat app via Android. If there is a problem related to the technical work, the party will contact IT by telephone or chat, sometimes IT negligent to inform its clients where the drive is completed or is working process. For that I created an application that aims to overcome it. IT is expected that the Helpdesk application uses the Knowlegde management System approach to shorten the time of problem handling, providing solutions to the same problem that does not reissue, provide a legitimate and controlled IT job report, and also achieve the objectives of the employment satisfaction to the workers.